Vzdělávání žáků se specifickými poruchami učení - matematika Metodická příručka - Blažková, Růžena (Masaryk University Press, 2020)
Title in English: Education of Pupils with Learning Disabilities - Mathematics. Education of pupils with learning disabilities has been in the centre of attention of teachers, parents as well as the general public. When solving our project we verified several ways of teaching mathematics at an ordinary primary school, which might help included pupils to handle some of their problems with this subject. Key activities had been prepared in order to introduce new approaches to teaching pupils with learning disorders in heterogeneous classes, with respect to development and strengthening of pupils' competences. Our project gave a positive outcome in changing attitudes of the included pupils to mathematics and improvement of their results. Also, the structured way of teaching mathematics helped most pupils in the class.